2019
DOI: 10.1098/rsbl.2018.0693
|View full text |Cite
|
Sign up to set email alerts
|

Rational choice of social group size in mosquitofish

Abstract: Choice of social group can affect the likelihood of survivorship and reproduction for social species. By joining larger social groups-shoalssmall freshwater fish like the mosquitofish Gambusia affinis can reduce predation risk and forage more efficiently. We tested shoal choice in mosquitofish to determine whether such choices are economically rational, i.e. consistent and optimal. Although many studies of decision-making assume rational choice, irrational decision-making is common and occurs across contexts. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Studies in another fish, the green swordtail, showed no evidence of a competitive decoy effect ( 92 ). Finally, a study of mosquito fish that was based on preference of group size, rather than characteristics of males per se, also failed to show such an effect ( 93 ).…”
Section: Cognition and Thinking About Mate Choicementioning
confidence: 99%
“…Studies in another fish, the green swordtail, showed no evidence of a competitive decoy effect ( 92 ). Finally, a study of mosquito fish that was based on preference of group size, rather than characteristics of males per se, also failed to show such an effect ( 93 ).…”
Section: Cognition and Thinking About Mate Choicementioning
confidence: 99%
“…The intrinsic flexibility of energy metabolism may play an important role in behavioral adaptation to the social environment, although we cannot provide strong evidence due to small sample sizes. It is interesting to note that some animals can rationally choose their social groups (Krause & Ruxton, 2002 ; Reding & Cummings, 2019 ). Therefore, individuals that differ in sociability may increase their fitness by choosing between different social groups to match their state to the group behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…The intrinsic flexibility of energy metabolism may play an important role in behavioral adaptation to the social environment, although we cannot provide strong evidence due to small sample sizes. It is interesting to note that some animals can rationally choose their social groups (Krause & Ruxton, 2002;Reding & Cummings, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Females from poeciliid species with high levels of sexual coercion like Gambusia employ shoaling as a strategy to reduce male harassment[27], and Gambusia females shoal more than males [22,36]. Female G. affinis have been shown to choose shoal group size in a rational manner [37]; and the benefit for selecting larger shoals can lead to both reduced male harassment and increased foraging efficiency in a closely related poecilid ( Gambusia holbrooki ) [38]. Increased shoaling tendencies in females may drive the shoaling-related cognitive advantage observed in G. affinis females as seen in our spatio-temporal learning task in which females were more successful than males in predicting the time and place of the shoal.…”
Section: Discussionmentioning
confidence: 99%